2000
DOI: 10.1177/008124630003000206
|View full text |Cite
|
Sign up to set email alerts
|

The Psychometric Properties of the Learning Style Inventory and the Learning Style Questionnaire: Two Normative Measures of Learning Styles

Abstract: David Kolb has provided a detailed, useful and widely accepted theory of experiential learning and learning styles. He developed the Learning Styles Inventory (LSI) to assess four learning abilities and four learning styles. Kolb's work is viewed favourably for establishing the existence of individual differences in learning styles, but the major criticism against his work is focused on his method of measuring learning styles and more specifically on the psychometric properties of the LSI. The LSI is an ipsati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 24 publications
2
13
0
Order By: Relevance
“…The 24 independent statements regarding one's preferred manner of information acquisition were scored on a 7-point Likert scale to determine a preference for either apprehension or comprehension. Previous studies have supported the high reliability, validity, and internal consistency of this version of Kolb's Learning Style Inventory (Pickworth and Schoeman, 2000;Willcoxson and Prosser, 1996).…”
Section: Learning Acquisition Modementioning
confidence: 54%
“…The 24 independent statements regarding one's preferred manner of information acquisition were scored on a 7-point Likert scale to determine a preference for either apprehension or comprehension. Previous studies have supported the high reliability, validity, and internal consistency of this version of Kolb's Learning Style Inventory (Pickworth and Schoeman, 2000;Willcoxson and Prosser, 1996).…”
Section: Learning Acquisition Modementioning
confidence: 54%
“…Like the LSI, the LSQ has been shown to be a reliable and valid instrument for assessing individual learning style preferences (Marshall & Merritt, 1986). Specifically, the LSQ has demonstrated content validity and has been recommended for use both in assessment of individual learning styles and for research purposes (Palermo et al, 2009;Pickworth & Schoeman, 2000). Permission to use the questionnaire was obtained from the authors.…”
Section: Methodsmentioning
confidence: 99%
“…In turn, these differences are impacting college students" ability to approach and gain new knowledge (otherwise known as their learning style), according to David Kolb"s theory of experiential learning (Palermo, Walker, Brown, & Zogi, 2009). Kolb"s theory has been previously detailed by many scholars (Austin, 2004;Heffler, 2001;Jones, Reichard, & Mokhtari, 2003;Palermo et al, 2009;Pickworth & Schoeman, 2000;Rassool & Rawaf, 2007;Wessel et al, 1999) and is based on an individual"s assessment of and ability to learn from experience. Kolb proposed that people have different approaches to perceiving, processing, and integrating information, which differ depending upon their circumstances and environment (Austin, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Evidence has shown that the use of ipsative personality tests is common within organisations for making pertinent decisions about people, which results in a comparison amongst people (Johnson et al, 1988;Martinussen, Richardsen & varum, 2001;Meade, 2004;Pickworth & Schoeman, 2000;Saville & Willson, 1991). Hence it is clear that there is still some confusion with regard to the use of ipsative instruments as tools for comparing people against one another.…”
Section: The Inherent Nature Of Ipsative Scalesmentioning
confidence: 99%